1998
DOI: 10.20506/rst.17.3.1122
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a reverse transcription-polymerase chain reaction assay and virus isolation for the detection of classical swine fever virus

Abstract: The authors evaluated the ability of a reverse transcription-polymerase chain reaction (RT-PCR) assay to detect classical swine fever virus (CSFV) in comparison with virus isolation and detection by an indirect immunoperoxidase assay (VI-IPA).To determine the specificity of the assay, samples from 60 spleens, 45 tonsils, ten submandibular lymph nodes, eight mesenteric lymph nodes and four kidneys, collected from pigs of various ages which had been slaughtered in abattoirs in Canada (a population free from CSFV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Generally, the antigen ELISA is used for intensive monitoring in large endemically infected areas. Although the antigen ELISA is considered not to be as sensitive for CSF diagnosis as virus isolation or RT-PCR (1,6,22,23), especially during the incubation period (11), experience in Germany has demonstrated that this method is suitable for routine diagnosis in large infected areas, if certain factors are taken into account (10). However, it should not be used during the final period of eradication; the authors recommend employing virus isolation or PCR within that period.…”
Section: Laboratory Diagnosis and Epidemiological Aspects Of Classica...mentioning
confidence: 99%
“…Generally, the antigen ELISA is used for intensive monitoring in large endemically infected areas. Although the antigen ELISA is considered not to be as sensitive for CSF diagnosis as virus isolation or RT-PCR (1,6,22,23), especially during the incubation period (11), experience in Germany has demonstrated that this method is suitable for routine diagnosis in large infected areas, if certain factors are taken into account (10). However, it should not be used during the final period of eradication; the authors recommend employing virus isolation or PCR within that period.…”
Section: Laboratory Diagnosis and Epidemiological Aspects Of Classica...mentioning
confidence: 99%